Relationship between microbial soil quality indicators and soil productivity under cassava-based farming systems in various sites in the Philippines - Monsalud, Rosario G.; Arguelles, Eldrin DLR.; Brown, Marilyn B.; Pedro, Mannix S.; Nepomuceno, Robert A.; Villadiego, Shaun Adrian D.; Monsalud, Florentino C. (2021)
Soil quality indicators are needed in monitoring the soil property transformations to determine sustainable farming systems. This study sought to determine the relationship between microbial soil quality indicators and soil productivity under cassava-based farming systems in the three major islands of the Philippines. The cassava-based farming systems of productive and marginal farms in each site were documented. Total microbial activity, bacterial diversity, abundance of arbuscular mycorrhizal fungi (AMF)spores, texture, and soil chemical properties were determined. The study showed a positive relationship between total microbial activity and soil productivity in one of the three study sites. The effectiveness of total microbial activity as a soil quality indicator is influenced by soil physical properties affecting drainage. The study also provided evidence on the consistent association of more diverse bacterial and higher AMF populations in productive soils under cassava-based farming systems in all three sites.
Keywords: Soil quality; Soil microbiology; Soil chemistry; Cassava--Soils.